Metodologia para implementação do MPS.BR utilizando o ambiente webapsee - ROCHA, Vanderlene Covre (Universidade Federal do Pará, 2011)
A number of initiatives to improve the software process has emerged recently to improve quality and productivity in software organizations. Some models and standards have focused the implementation of improvements in the software development process area; MPS.BR model is an example of thiese models. This process improvement model aims to improve software quality, preferably for micro, small and medium enterprises in order to meet the needs of their business model and was chosen to be explored in this work. Several advantages are gained during process improvement effort, one of them is the definition of a systematic process for software development, which helps to achieve the process quality and productivity and also the developed product quality. The use of a defined process model brings several benefits associated with standardization, such as the optimization, the re-work cost reduction, less defects in products, among others. But there is a lack of models that can be applied directly to a specific company of software development and therefore it is necessary to model the process, customizing it with the ultimate goal of creating a model that adequately represents the organization process. One of the difficulties for the implementation of models such as MPS.BR is the lack of methodologies that shows how the implementation of improvements to be made and not only what should be done. In this context, this work proposes a methodology for the implementation of the MPS.BR model based on IDEAL model, through a specific tool, called WebAPSEE, which works to coordinate the methodology execution. The methodology was tested in a local organization called CTIC - Center for Information Technology and Communication of UFPA which was assessed as level of G MPS.BR.